Challenges and strategic opportunities for Brazils participation in global value chains Francielly de Fátima Almeida and Luciano Nakabashi - United Nations Economic Commission for Latin America; the Caribbean (CEPAL Review, 2024)
The objective of this study is to measure the effects of global value chain participation on the total factor productivity of the Brazilian economy, using heterogeneous dynamic panel models and methods suitable for diagnosing short-run and long-run effects. The study has two innovative features: it estimates the impact of global value chains on Brazil’s sectoral total factor productivity by disaggregating the indicators of simple and complex value chain participation developed by Wang and others (2017), and it uses a novel methodology to analyse the relationship between participation in global value chains and sectoral total factor productivity in Brazil. In the long run, this participation appears to generate productivity gains whatever indicator is considered, with the largest long-run effects arising when activities are carried out in complex chains. Positive effects are found in 15 of the 31 sectors analysed.